Pengaruh Penerapan Model Pembelajaran PBL terhadap Hasil Belajar Kognitif Choux Paste di SMKN 2 Mojokerto - Putri Azizah Indrasara; Asrul Bahar; Nugrahani Astuti; Ila Huda Puspita Dewi (Pusat Riset dan Inovasi Nasional, 2023)
This research aims to determine the effect of applying a problem-based learning model with the following variables: 1) teacher activity, 2) student activity, and 3) cognitive learning outcomes of grade XI students, on competency standard choux paste at SMKN 2 Mojokerto. This type of research is experimental with a pretest-posttest control group design and uses two classes that act as experimental and control classes. The instruments used were pretest-posttest questions and observation sheets of teacher and student activities. Data analysis was carried out by independent sample t-test using SPSS 25 for Windows. The results of the independent sample t-test test for the pretest showed that the pretest in the two classes was not significantly different and it could be concluded that the two classes had the same initial ability. While the results of the independent t-test test for the posttest obtained a Sig. (2-tailed) of 0.034 which means that the significance value is <0,05. The conclusions on the results of this research are: 1) teacher activity is classified in the very good category, 2) student activity is classified in the very good category, and 3) student's cognitive learning outcomes in the experimental class have increased more than the control class.